This bird has flown ebook - Hoffs, Susanna (2023)
This delightfully funny and steamy novel about music, fate, and love from beloved songwriter and Bangles co-founder Susanna Hoffs is "a total knockout" and "the smart, ferocious rock-star redemption romance you didn’t know you needed" ( New York Times Book Review). " This Bird Has Flown is SO GOOD. If you liked Daisy Jones & The Six or Juliet, Naked , I feel like you will love this one." —Taylor Jenkins Reid Jane Start is thirty-three, broke, and recently single. Ten years prior, she had a hit song—written by world-famous superstar Jonesy—but Jane hasn’t had a breakout since. Now she's living out of four garbage bags at her parents’ house. Rock bottom. But when her longtime manager Pippa sends Jane to London to regroup, she’s seated next to an intriguing stranger on the flight—the  other  Tom Hardy, an elegantly handsome Oxford professor of literature. Jane is instantly smitten by Tom, and soon, truly inspired. But it’s not Jane’s past alone that haunts her second chance at stardom, and at love. Is Tom all that he seems? And can Jane emerge from the shadow of Jonesy's earlier hit, and into the light of her own? In turns deeply sexy, riotously funny, and utterly joyful,  This Bird Has Flown  explores love, passion, and the ghosts of our past, and offers a glimpse inside the music business that could only come from beloved songwriter Susanna Hoffs. "Hoffs nails the life and heartbreak of rock and roll, academia, and our soul-nourishing connection to our very own soulmate so expertly she must have carved it in Norwegian Wood! And isn't it good!" —Tom Hanks "A sweet and tender romance —and a valentine to music." —NPR "This book will hook you like the best pop song you can't stop playing — something Susanna knows a little something about!" —Molly Ringwald "This isn’t just a book, it’s a love song, and it should come as no surprise that Susanna Hoffs has crafted the perfect one to put on your playlist.” ―Christina Lauren “This book is a blast . . . about art and new beginnings and love and friendship and taking risks, it’s such a fun read.” ―Jasmine Guillory